2016
DOI: 10.1371/journal.pone.0165637
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Studying the Physiology and Pathophysiology of Myelinated and Non-Myelinated Axons in the CNS White Matter

Abstract: Advances in brain connectomics set the need for detailed knowledge of functional properties of myelinated and non-myelinated (if present) axons in specific white matter pathways. The corpus callosum (CC), a major white matter structure interconnecting brain hemispheres, is extensively used for studying CNS axonal function. Unlike another widely used CNS white matter preparation, the optic nerve where all axons are myelinated, the CC contains also a large population of non-myelinated axons, making it particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 92 publications
(158 reference statements)
0
22
0
Order By: Relevance
“…Parameters of the N1 (myelinated axons) and N2 (unmyelinated axons) components of the CAPs were contrasted in the anterior CC after cuprizone and L‐NIO induced WM injury mouse models. Brain slices from the anterior CC were chosen for this comparative analysis, similar as a previous study, our data presented in the current study have showed that the anterior CC contains a higher proportion of myelinated axons than the posterior CC. The results indicated that the parameters beyond the amplitude and the area of the N1 component of the CAPs might be used to distinguish between either pure demyelination or demyelination concurrent with axonal injury.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Parameters of the N1 (myelinated axons) and N2 (unmyelinated axons) components of the CAPs were contrasted in the anterior CC after cuprizone and L‐NIO induced WM injury mouse models. Brain slices from the anterior CC were chosen for this comparative analysis, similar as a previous study, our data presented in the current study have showed that the anterior CC contains a higher proportion of myelinated axons than the posterior CC. The results indicated that the parameters beyond the amplitude and the area of the N1 component of the CAPs might be used to distinguish between either pure demyelination or demyelination concurrent with axonal injury.…”
Section: Discussionmentioning
confidence: 54%
“…The early peak (N1) signifies the conduction of myelinated axons, while the later phase peak (N2) represents unmyelinated axons. Previous research has observed heterogeneity in the CAPs response within the rostral‐caudal extent of the CC that appears to be linked to variations in the proportion of myelinated and unmyelinated axons . We therefore surmised that demyelination and axonal damage might give different CAPs profiles relative to the normal CAPs response.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with the functional readout applied, the measuring of compound action potentials. While it is generally assumed that the two peaks that are usually measured when recording CAPs in fibers of the corpus callosum belong to myelinated and unmyelinated fibers , the ratio between these two peaks is highly depending on positioning of the electrodes [summarized in ]. After complete demyelination in the corpus callosum, the first of the two peaks is lost .…”
Section: Discussionmentioning
confidence: 99%
“…Corpus callosum samples were prepared as described previously (Li et al , ). Briefly, coronal brain sections (400 ÎŒm) containing the corpus callosum were sliced in aCSF using a vibratome (VT1200s, Leica).…”
Section: Methodsmentioning
confidence: 99%